Synthesis, characterization, and anti-plasmodial activity of 2,6-substituted benzothiazole derivatives (Bangladesh Journal of Pharmacology, 2016)
Six compounds of benzothiazole derivatives were synthesized, and structures were confirmed by FT-IR, 1H-NMR, 13C-NMR and LC-MS. The resulting compounds were evaluated for anti-plasmodial activity against Plasmodium falciparum by Giemsa stain. Among them the compounds 3b and 4 showed potent anti-plasmodial activity against P. falciparum. The compounds 3a, 5a, 5b also showed moderate anti-plasmodial activity. The structure-activity relationships of benzothiazole derivatives also discussed which were useful for exploring and developing benzothiazole derivatives as novel anti-malarial drugs.